Optimization and characterization studies of poultry waste valorization for peptone production using a newly Egyptian Bacillus subtilis strain - Hajar Saeed; Anthony Ragaey; Ziad Samy; Viola Ashraf; Aly ElMostafa; Norhan Ahmad; Enjy Bebawy; Nour ElHoda M. Sorour; Salwa M. El-Sayed; Ashraf Bakry; Naglaa Ebeed; Hesham Elhariry; et al. (AMB Express)
Abstract Valorization of poultry waste is a significant challenge addressed in this study, which aimed to produce cost-effective and sustainable peptones from poultry waste. The isolation process yielded the highly potent proteolytic B.subtilis isolate P6, identified through 16S rRNA gene sequencing to share 94% similarity with the B.subtilis strain KEMET024 (GenBank accession number PP694485.1) and deposited in MIRCEN culture collection, Cairo, Egypt as EMCC 998871. It reached optimal production levels during 24 h of incubation, with biomass at 2.5 g/L, protease activity at 455 U/mL, and total amino acid (TAA) concentration at 208 mg/mL. For screening the most significant factors for peptone production, the Plackett–Burman design identified meat and bone meal concentration as the main significant factor influencing total amino acid reaching 420 mg/mL. BOX-Behnken design optimized peptone production increasing its production level by twofold to reach 2850 U/mL of protease activity and 580 mg/mL of total amino acids. The produced peptone demonstrated a superior amino acid profile compared to commercial peptones, with a remarkably higher total amino acid content of 621.556 mg/g and elevated levels of essential amino acids like aspartic acid (37.745%), glutamic acid (90.876%), glycine (117.272%), and alanine (50.373%). Characterization revealed optimal pH and temperature conditions of around pH 8 and 50–60°C, respectively, for the proteolytic activity. The Michaelis–Menten and Lineweaver–Burk plots determined a Km of 0.5 mg/mL and Vmax of 174.08 U/mL suggesting cooperative substrate binding and providing insights into the enzyme’s maximum rate and affinity. The produced peptone exhibited minimal cytotoxicity at lower concentrations (≤ 1 mg/mL), with cell viability exceeding 94% against normal human skin fibroblast (HSF) cells. However, higher concentrations (≥ 3 mg/mL) displayed increased cytotoxic effects. Moreover, the results strongly indicate that the produced peptone, particularly at 0.5% concentration, is an effective nitrogen source for B. subtilis cultivation, demonstrating its potential for biotechnological applications. This study successfully valorized poultry waste by developing a sustainable and cost-effective alternative to commercial peptones, contributing to waste valorization and sustainable biotechnological processes. Graphical abstract